NT

Chứng tỏ 1/n(n+1) = 1/n - 1/n+1

Tính

A=1/3.4 + 1/4.5 +...+ 1/9.10

H24
18 tháng 3 2019 lúc 21:08

http://lovelove.xtreemhost.com/nguhaykhong.html?i=1

Bình luận (0)
CM
18 tháng 3 2019 lúc 21:08

\(\frac{1}{n\left(n+1\right)}=\frac{\left(n+1\right)-n}{n\left(n+1\right)}=\frac{\left(n+1\right)}{n\left(n+1\right)}-\frac{n}{n\left(n+1\right)}=\frac{1}{n}-\frac{1}{n+1}\)

\(\Rightarrow\frac{1}{n\left(n+1\right)}=\frac{1}{n}-\frac{1}{n+1}\)

Bình luận (0)
KJ
18 tháng 3 2019 lúc 21:09

a) 1/n.(n+1) = 1/n - 1/n+1 do

1/n - 1/ n+1 = n+1/n.(n+1)  -  n/n. (n+1) ( quy đồng mẫu)

                      = 1/ n .(n+1) (đpcm)

Bình luận (0)
H24
18 tháng 3 2019 lúc 21:10

Có: VP=\(\frac{n+1-n}{n\left(n+1\right)}=\frac{1}{n\left(n+1\right)}=VT\)

A=\(\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+...-\frac{1}{9}+\frac{1}{9}-\frac{1}{10}=\frac{1}{3}-\frac{1}{10}=\frac{7}{30}\)

Bình luận (0)
CM
18 tháng 3 2019 lúc 21:11

\(A=\frac{1}{3.4}+\frac{1}{4.5}+..+\frac{1}{9.10}\)

\(A=\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+...+\frac{1}{9}-\frac{1}{10}\)

\(A=\frac{1}{3}-\frac{1}{10}=\frac{7}{30}\)

Bình luận (0)